Efektifitas Badan Hak Asasi Manusia Asean dalam Menangani Isu Hak Asasi Manusia dalam Regional Asean - Lili Husni Putri (Universitas Syiah Kuala, 2013)
ABSTRACT: The Association of South East Asian Nations was established as a political and economic entity through Bangkok Declaration in 1967. Among its seven objectives are: to accelerate growth, social progress and cultural development, to promote regional peace and stability through abiding respect for justice and the rule of law in the relationship between countries in the region and adherence to the principle to the United Nations Charter. Although the term ‘human rights’ is not explicitly used in the Declaration, by affirming adherence to the principle of the United Nations Charter, the founding members of ASEAN accepted its purposes and principles. The Association of South East Asian Human rights issues and the establishment of Association South East Asian Nations (ASEAN) human rights mechanism are still very challenging matters for ASEAN. Generally speaking, ASEAN has been making a slow progress in the field of human rights. ASEAN has long empashized that the promotion and the protection of human rights by the international community must recognize national sovereignty, national border and non-interference in another state’s affairs. ASEAN views human rights as an internal affairs. The establishment of human rights mechanism was provided for by the Charter but what kind of human rights body ASEAN would be comfortable with was a crucial question for ASEAN and its people. Through the setting up of ASEAN Human Rights Body, this paper aims to examine the effectiveness of the ASEAN Human Rights Body in dealing with human rights issues in ASEAN region. The Effectiveness of Asean Human Rights Body in Dealing With Human Rights Issues in Asean Region